MENELUSURI TEORI CHAOS DALAM HUKUM MELALUI PARADIGMA CRITICAL THEORY - Faisal, Faisal (Yustisia, 2014)
AbstractThe paper will study a dialectic domain of chaos theory of Charles Sampford’s law by using critical theory paradigm. The paper will present results of the study as follow: first, melee concept of chaos theory in any law may be uniformed by using ontological paradigm of the critical theory based on historical realism. Second, an intercept of ideas segments of Sampford’s chaos theory as a critical body can be seen from its paradigm epistemology they had built. Sampford developed his epistemology, namely both interpreter and reality are dialectic; the statement is similar with dialogic-dialectic’s one of critical paradigm. Third, the equality of essences between Sampford’s chaos theory and critical theory might be measured if methodological presentation of the critical theory paradigm about transactional-subjectivist is examined. Therefore, the reality is understood completely, impartially or mechanistically. As does chaos theory, Sampford elaborated it in his dialectical-integrative methodology, actually chaos theory of Sampford is trying to reject dualistic’s and reductionist’s view of points in attempts of making the reality is still intact. Based on what is held by critical cliques that the analysis focus will be based on contextual matter. AbstrakTulisan ini akan di arahkan untuk menelusuri ruang dialektis teori chaos dalam hukum charles Sampford dengan paradigma citical theory. Sebagaimana penelusuran yang dapat disajikan dalam tulisan ini, adalah; pertama, konsep melee dalam teori chaos dalam hukum dapat saja di seragamkan dengan ontologi paradigma critical theory dimana berpijak pada realisme historis. Kedua, bertemunya ruas berfikir teori chaos Sampford sebagai sosok critical dapat dilihat dari epistemologi paradigma yang dibangun keduanya. Sampford membangun epistemologinya yaitu penafsir dan realitas itu dialektis, hal ini senada dengan dialogis-dialektikal yang dimiliki paradigma critical. Ketiga, kesepadanan esensi antara teori chaos Sampford dan critical dapat saja terukur bila melihat sajian metodologi paradigma critical mengenai transaksional-subjektivis. Dengan demikian realitas di pahami secara utuh tidak parsial ataupun mekanistik. Sebagaimana teori chaos Sampford menguraikan hal ini pada metodologi dialektikal- integratif, sejatinya teori chaos Sampford sedang menolak pandangan dualistik dan reduksionis agar realitas terlihat lebih utuh. Berdasarkan dengan apa yang di anut oleh kalangan critical bahwasannya fokus analisa akan di dasarkan pada hal yang kontekstual.Kata kunci: Teori chaos, Teori Kritis, Paradigma, Positivisme Hukum